Diversity Management and Cultural Competency of Teacher Candidates in Blacksea Region of Turkey - Güngör, Tuba Aydın; Çakır, Çiğdem (Journal of Education in Black Sea Region, 2021)
Ever since the world has been dealing with the problem called Covid-19, everything around us has had to change. This epidemic has affected our lives in many ways and has set us completely new roles and tasks on many things, and education which is one of the most important things among them had been changed. Indeed, the transformation of education had already begun with the improvement of transportation and telecommunication conditions and being able to receive education online in different countries or via the internet has brought new concepts to the academic world. Cultural competence, one of them, is shaped by identity and traditions, thus cultural diversity is the main factor in determining the characteristics of this concept. Meanwhile, the ones who realize the acculturation of the society, the people who created this concept, are the teachers who direct the society in both academic and cultural dimensions. As a result, teachers need to learn to manage diversity to be able to cope with the differences in their classrooms, as they encounter many different cultural characteristics. For this reason, in this study, it is considered worth investigating what kind of dimensions pre-service teachers can have regarding the management of diversity and cultural competencies. The of the research consists of 1073 teacher candidates studying in Artvin Coruh University. The aim of this research was to reveal the diversity management skills and cultural competence levels of education faculty students. In order to reach more in-depth information on what management of diversity and cultural competencies is, the study started with a literature review. Then, Diversity Management Scale (DMS) and Cultural Competence Scale (CCS) were applied to Artvin Çoruh University, in the Black Sea region of Turkey, to faculty of education students (teacher candidates). After the regression analysis of the data for the management of diversity scale, two dimensions have been found which are managerial practices and managerial approaches. Moreover, for the cultural competencies scale, three dimensions were found which are cultural knowledge, cultural sensitivity, and cultural skills. Lastly, a significant relationship was found between Diversity Management and Cultural Competence of the teacher candidates, and cultural competence was found to be a meaningful predictor of diversity management of teacher candidates. Keywords: diversity, culture, cultural competence, diversity management, teachers